2007
DOI: 10.1007/s00595-007-3519-3
|View full text |Cite
|
Sign up to set email alerts
|

Perforation of Meckel's Diverticulum Manifesting as Aseptic Peritonitis in a Neonate: Report of a Case

Abstract: We report a case of perforated Meckel's diverticulum with aseptic peritonitis in a 17-day-old neonate. The baby had been brought to the hospital with fever and abdominal distention. Abdominal computed tomography showed a 5-cm abscess in the lower abdomen, and emergency laparotomy was performed for suspected perforated appendicitis. However, we found a perforated Meckel's diverticulum. No bacteria were detected in the purulent ascites from the peritoneal cavity. We speculate that the narrow lumen between the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Other investigations included ultrasonography (US) and computed tomography (CT), which were found to be unnecessary when plain radiographs revealed pneumoperitoneum. In the study by Oyachi et al [19], abdominal CT showed an intraabdominal mass/abscess in a neonate who was found to have a perforated MD at laparotomy. In another study, abdominal US showed ascites, which was secondary to a perforated MD [15].…”
Section: Discussionmentioning
confidence: 96%
“…Other investigations included ultrasonography (US) and computed tomography (CT), which were found to be unnecessary when plain radiographs revealed pneumoperitoneum. In the study by Oyachi et al [19], abdominal CT showed an intraabdominal mass/abscess in a neonate who was found to have a perforated MD at laparotomy. In another study, abdominal US showed ascites, which was secondary to a perforated MD [15].…”
Section: Discussionmentioning
confidence: 96%
“…Most of these are asymptomatic and occur during childhood in the first two years of life, with a male-to-female ratio of 2:1 [2]. The most common symptoms are gastrointestinal bleeding, bowel obstruction and diverticulitis [20].…”
Section: Discussionmentioning
confidence: 99%
“…In our case radiological exploration was not helpful. Perforated Meckel's diverticulum is rarely found in neonates [5]. To summarize, neonatal intussusception is an extremely rare clinical entity.…”
Section: Dear Sirmentioning
confidence: 96%